ASSESSMENT OF KNOWLEDGE ATTITUDE, AND PRACTICES OF NURSES REGARDING COLOSTOMY CARE - RAHEEM, A; SADDIQUE, H; TASNEEM, SS (Biological and Clinical Sciences Research Journal, 2024)
Colostomy care is a critical aspect of nursing practice that requires comprehensive knowledge, positive attitudes, and effective practices. Nurses play a pivotal role in managing colostomies and ensuring optimal patient outcomes. However, gaps in knowledge and practices persist, particularly in resource-limited settings, impacting the quality of care delivered. Objective: To assess the knowledge, attitudes, and practices of nurses regarding colostomy care and identify areas requiring improvement. Methods: A quantitative cross-sectional study was conducted at a tertiary care hospital in Lahore, Pakistan. A total of 150 nurses from medical, surgical, and other departments were recruited using convenient sampling. Data were collected using a validated questionnaire covering demographic characteristics, knowledge, attitudes, and practices related to colostomy care. Descriptive and inferential statistics were used for analysis, with results presented as frequencies and percentages. Results: The study revealed that 84.0% of participants correctly identified the relationship between colostomy output and its anatomical location, and 79.3% were aware of odor-reduction filters for ostomy bags. Positive attitudes were prevalent, with 87.3% reporting confidence in providing stoma care. Adherence to hand hygiene practices before and after procedures was 100.0%, reflecting excellent hygiene compliance. However, 26.7% did not address physical problems related to stomas, and 43.3% expressed neutrality about access to expert staff for colostomy care. Conclusion: Nurses exhibit commendable knowledge and practices in colostomy care, yet systemic barriers such as limited access to expert staff and inconsistent training opportunities impact care quality. Enhancing institutional support and providing targeted education can bridge these gaps, empowering nurses to deliver optimal care and improve patient outcomes.